ANALISIS PENGARUH CURRENT RATIO, DEBT TO EQUITY RATIO, QUICK ASSET TO INVENTORY RATIO, DAN RETURN ON ASSET TERHADAP RETURN SAHAM - Nur Tri Kadarini (Magister Ilmu Akuntansi Universitas Jambi, 2015)
Goals to be achieved from this research is to exam and provide empirical evidence effect of significant of current ratio, debt to equity ratio, Quick inventory of assets to and return on assets of the company's stock returns on food, beverages, and medications - drugs in IDX either partially or simultaneously. This study is an empirical study on the company's food, drinks, and drugs - drugs that are listed in the Indonesia Stock Effects in the period 2008 - 201 2 presented in Indonesian Capital Market Directory (ICMD) and data from www.bei.co.id and http: / / www.idx.co.id . Research methods and approach using research explanations (explanatory research) is research that highlights the relationship between the study variables and test hypotheses that have been formulated before the focus lies in the explanation of the relationship between variables. Type of explanatory research aims to determine the size of the relationship of a variable to other variables, and to test hypotheses proposed (accepted or rejected). The instrument used in this study statistics with multiple linear regression analysis to determine the level of the relations and financial ratios as a tool The main analysis. Result of testing the hypothesis of the study during the period of 2008 to 2012, it can be concluded that partial Current Ratio and Quick Asset Ratio to significant effect on Stock Return, while the Debt to Equity Ratio, Inventory and Return on Assets ratio no significantly influence the company's Return on Equity food, beverages, and medications - drugs in IDX. Concurrent (simultaneous) Current ratio, Debt to Equity Ratio, the Quick Inventory of assets to, and Return on Assets are together - at significant effect on stock returns in the company of food, beverages, and medications - drugs in IDX. Keywords: Current Ratio, Debt to Equity Ratio, Quick Ratio Asset Inventory and Return to Shareholders